Effects of Clostridium perfringens alpha and epsilon toxins in the bovine gut - Morris, Winston Eduardo (2012)
Clostridium perfringens alpha and epsilon toxins produce enterotoxaemia in sheep and goats. However, the information regarding the pathophysiology of alpha and epsilon toxins in the bovine intestine is still scanty. In this study, intestinal loops were performed in the ileum and colon of three one-week-old Holstein and two four-week-old crossbreed calves. Laparotomy was performed in all calves under anaesthesia and four loops -three cm long- were performed in the small and large intestines. For both intestines, loops were inoculated with alpha or epsilon toxins. Tissue samples from all loops were obtained and processed for routine histology and for transmission electron microscopy. Congestion was observed in toxin treated loops. Fluid accumulation in the gut lumen was prominent in all treated loops, but in epsilon treated ones the mucous was also haemorrhagic. The histology revealed large amount of exfoliated epithelial cells in the lumen of alpha toxin treated loops and severe haemorrhage was observed in the lamina propria of epsilon toxin treated colonic loops. Despite some necrotic exfoliated enterocytes, no ultraestructural changes were observed in alpha toxin treated loops, though with epsilon toxin the loops exhibited dilation of the intercellular space in the mucosa of both, small and large intestines. These observations indicate that both, alpha and epsilon toxins can alter the intestinal barrier, in calves and are pathogenic for this species.